2020
DOI: 10.4136/ambi-agua.2592
|View full text |Cite
|
Sign up to set email alerts
|

Ozonation as a pre-treatment of landfill leachate

Abstract: Ozone is an oxidizing agent with a potential for removing complex molecules, including those of difficult microbiological decomposition, such as the molecules found in landfill leachates. This effluent presents high organic content, including recalcitrant molecules. Therefore, this study evaluated the efficiency of ozonation in the treatment of raw leachate at the Primavera landfill, located in Mato Grosso, Brazil. The experiments were carried out using the batch system. The leachate pH value was set at 7 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 32 publications
(37 reference statements)
0
1
0
Order By: Relevance
“…It was found that the TOC removal efficiency was 37% (346 mg dm −3 ) after 60 min of ozonation. More recently, Hoffmann et al (2020) assessed the efficiency of ozonation in the treatment of raw LFL. Runs were carried out using a batch system.…”
Section: Ozonationmentioning
confidence: 99%
“…It was found that the TOC removal efficiency was 37% (346 mg dm −3 ) after 60 min of ozonation. More recently, Hoffmann et al (2020) assessed the efficiency of ozonation in the treatment of raw LFL. Runs were carried out using a batch system.…”
Section: Ozonationmentioning
confidence: 99%